2019
DOI: 10.1111/papr.12807
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Chronic Opiate Therapy After Successful Spinal Cord Stimulation Is Highly Dependent Upon the Daily Opioid Dose

Abstract: Objectives The aim of this study was to determine if any of the factors recorded on a standard clinical history of a patient considered for spinal cord stimulation (SCS) would be associated with reduction or cessation of opioids following implantation. Design Retrospective, single academic center. Methods Patients included in the chart analysis underwent implantation of percutaneous SCS devices from 1999 to 2015 with follow‐up until the end of September 2018. Patients who achieved at least an average of 50% pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The conventional treatments used in this type of patients may not only not reduce the symptoms completely but can also entail side effects and restrictions in the daily life of the patients. Patients treated conventionally, may require interventional treatments that allow for the reduction of medication prescribed, such as SCS, a therapy that masks pain signals before they reach the brain (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional treatments used in this type of patients may not only not reduce the symptoms completely but can also entail side effects and restrictions in the daily life of the patients. Patients treated conventionally, may require interventional treatments that allow for the reduction of medication prescribed, such as SCS, a therapy that masks pain signals before they reach the brain (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis of insurance claim data in patients who were chronic opioid users before receiving conventional SCS showed that daily opioid doses of less than 65 MME at the start of SCS treatment were predictive of reduced opioid use in response to stimulation therapy [27]. A single-center retrospective study of patients who received low-frequency SCS for refractory neuropathic pain similarly reported that baseline opioid use of ≤30 MME daily was predictive of opioid cessation and that most responders (≥50% pain relief ) did not reduce opioid use over the course of the study [28]. Likewise, a retrospective study in over 631 patients who received intrathecal drug administration for chronic, noncancer pain also found that baseline systemic opioid dose was strongly correlated with whether patients would discontinue opioid use during the following year, with those taking less than 50 MME being twofold more likely to stop opioid use than those taking 90 MME or more [29].…”
Section: Discussionmentioning
confidence: 99%
“…32 Although these studies have been primarily focused on the outcome of pain reduction and responder rate, defined as the proportion of patients who experience at least 50% pain reduction without any neurologic deficits, many include assessments of pain medication use among reported secondary outcomes. Conventional SCS treatment has been shown to be associated with reduction in conventional opioid dose and stabilization of usage in two large retrospective studies by Sharan et al and Simopoulos et al 33,34 Multiple systematic reviews also demonstrated increased odds of reducing pain medication in patients with intractable pain follow-ing SCS treatment. 35,36 Considering the potential advantages of 10 kHz SCS, this review was conducted to summarize the current landscape of evidence in the medical literature regarding the efficacy of 10 kHz SCS to both treat pain symptoms and reduce the amount of conventional opioid analgesics required by patients with chronic, noncancer pain.…”
Section: High-frequency Scs At 10 Khz (Hf10)mentioning
confidence: 99%
“…Conventional SCS treatment has been shown to be associated with reduction in conventional opioid dose and stabilization of usage in two large retrospective studies by Sharan et al . and Simopoulos et al . Multiple systematic reviews also demonstrated increased odds of reducing pain medication in patients with intractable pain following SCS treatment .…”
Section: Introductionmentioning
confidence: 96%